Handbook of chemical processing equipment - Cheremisinoff, Nicholas P.
A practical reference on process equipment, this book provides practical understanding and description of the working principles, intended applications, selection criteria and fundamental design principles for equipment used throughout the process and allied chemical industries. It describes unit operations and equipment.